Balance performance of healthy young individuals in real versus matched virtual environments: a systematic scoping review - Schedler, Simon; Gramann, Klaus; Hill, Mathew W.; Muehlbauer, Thomas (Frontiers in Human Neuroscience, 2024)
Background Due to technological advancements and the development of consumer-oriented head mounted displays (HMDs), virtual reality (VR) is used in studies on balance performance and balance trainability more and more frequently. Yet, it may be assumed that balance performance is affected by the physical characteristics of the HMD (e.g., weight) as well as by the virtual visual environment. Moreover, it has been shown that balance is age-dependent with children and adolescents showing worse performances compared to young adults, which may also affect their balance performance in virtual environments. Objectives The present systematic scoping review aims to provide an overview on the current evidence regarding balance performance of healthy, young individuals (6–30 years) in real and matched virtual environments. Methods A systematic literature search in the electronic databases PubMed, Web of Science, and SPORTDiscus (from their inception date to February 2024) resulted in 9,554 studies potentially eligible for inclusion. Eligibility criteria were: (i) investigation of healthy, young individuals (6–30 years), (ii) balance assessment in the real and a matched virtual environment, (iii) use of a fully immersive HMD, (iv) reporting of at least one balance parameter. A total of 10 studies met the predefined inclusion criteria and were thus included in this review. All studies were conducted with healthy, young adults (19–30 years). Results Five studies assessed static balance, four studies quantified dynamic balance, and one study measured static as well as dynamic balance performance. In healthy young adults, static balance performance was similar with and without VR during simple standing tasks (e.g., two-legged stance), but worse in VR during more challenging tasks (e.g., one-legged stance). Concerning dynamic balance, four out of five studies reported worse performance in VR, while one study did not find differences between visual environments. Most importantly, none of the studies investigating healthy children (6–12 years) and/or adolescents (13–18 years) met the predefined inclusion criteria. Conclusion In healthy young adults, balance performance seems to be affected by VR only during challenging static (e.g., one-legged stance) as well as during dynamic balance tasks. The underlying causes remain unclear, but factors such as perceived presence in VR, a shift in sensory organization and/or perceptual distortion may play a role. Of particular importance is the finding that there is a void in the literature on the influence of VR on balance performance of healthy children and adolescents.